Tahap Kemahiran Peserta Didik Menulis dan Membaca Alquran di Madrasah Aliyah - Hafizul Hamdi; Vinni Sabrina; Lailan Najmah (Murabby: Jurnal Pendidikan Islam, 2024)
This research aims to determine the level of proficiency in reading and writing the Alquran, especially at the Madrasah Aliyah level. This research uses quantitative methods with a descriptive type. Meanwhile, the data source was taken using a questionnaire from forty students consisting of three class levels, namely class X to class simple random sampling. Questionnaire data was analyzed descriptively using software IBM SPSS statistics. The results of the analysis show two levels of students' skills in reading and writing the Alquran at Madrasah Aliyah, namely i) the students' ability to read the Alquran is already at a good level, seen from the aspect of the alphabet and tajwid, ii) able to write the Alquran clearly and accurately in the aspect of linking letters and give movement. This finding can be a source of reading material and a wealth of articles about the ability of students to read and write the Alquran.